Royal Mistress Monica Mason remembers, an interview - Wainwright, Steven P. (Dance Books Ltd., Alton,Hampshire (UK), 2001)
Monica Mason talks. All of us in the corps de ballet were worn to a frazzle. I think we were probaly used and abused, but we didn't mind. We were seeing America from coast to coast. It was early days and the survival of the company was the most important thing... As time's gone on, everywhere in society, no longer does one sell one's soul for a company. Rudolf had this passionate relationship with Erik Bruhn - he would have adored to have been Erik and Erik wanted to be Rudolf. There were we in the middle looking at these two great male dancers. PALABRAS CLAVE: Monica Mason, life and career, Royal Ballet, The Rite of Spring.